2012
DOI: 10.1590/s1516-35982012000700020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different digestible isoleucine/lysine ratios for broiler chickens

Abstract: Two experiments were conducted to evaluate different digestible isoleucine/lysine ratios on diets for broiler chickens in the starter (7 to 21 days) and finishing (30 to 43 days) phases. For the tests, the experimental design was of randomized blocks with seven treatments (six different digestible isoleucine/lysine ratios and a control treatment) and eight repetitions of 25 and 20 birds (COBB males) per experimental unit in the starter and finishing phases, respectively. The diets met the requirements, except … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 4 publications
(7 reference statements)
1
8
0
Order By: Relevance
“…Current analysis shows that the isoleucine requirement for the carcass parameters assessed at 42 days is lower than the requirement for performance. These results agreeing with findings by Corzo et al (2008) who tested 0.58; 0.66 and 0.68% of digestible isoleucine levels in broilers' diets and Tavernari et al (2012) who evaluated different digestible isoleucine/lysine ratios (58.0; 62.0; 66.0; 70.0; 74.0 and 78.0%) on diets for broilers in the finishing (30 to 43 days) phase. Berres et al (2010) likewise evaluated broilers fed on diets with increased Val-and Ile-to-Lys ratios from 14 to 35 days and registered no differences in the treatment for carcass evaluation at 35 days.…”
Section: Effect On the Weight Of Several Parts In Broilerssupporting
confidence: 90%
See 2 more Smart Citations
“…Current analysis shows that the isoleucine requirement for the carcass parameters assessed at 42 days is lower than the requirement for performance. These results agreeing with findings by Corzo et al (2008) who tested 0.58; 0.66 and 0.68% of digestible isoleucine levels in broilers' diets and Tavernari et al (2012) who evaluated different digestible isoleucine/lysine ratios (58.0; 62.0; 66.0; 70.0; 74.0 and 78.0%) on diets for broilers in the finishing (30 to 43 days) phase. Berres et al (2010) likewise evaluated broilers fed on diets with increased Val-and Ile-to-Lys ratios from 14 to 35 days and registered no differences in the treatment for carcass evaluation at 35 days.…”
Section: Effect On the Weight Of Several Parts In Broilerssupporting
confidence: 90%
“…Campos et al (2012) analyzed the effect of isoleucine: lysine ratio on broiler performance and observed that 69% isoleucine: lysine ratio was recommended for maximum performance of broilers from 28 to 40 days old. According to Tavernari et al (2012), the best isoleucine: lysine ratios for feed intake, weight gain and feed conversion were 64, 68 and 72%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The deficiency of SLAA resulted in significantly lower absolute intake of valine and isoleucine (in T 2 ) and additionally tryptophan (in T 3 ; Table-6 ) which perhaps impeded protein accretion and hence the growth performance of broilers, since AA have been revealed to influence the myogenic gene expression in broilers [ 16 ]. The growth retardation as a consequence to SLAA deficiency is well noticed in previous studies with deficiencies of valine alone in young broilers [ 17 , 18 ], valine and isoleucine [ 1 , 19 ], isoleucine, tryptophan and arginine [ 20 ], isoleucine alone [ 21 , 22 ] and arginine, valine, isoleucine and tryptophan [ 23 ]. With marginal SLAA deficiency in the finisher phase, birds could compensate to the SLAA intake at this time period (data not shown) and as a consequence, birds could grow on par with control which is suggestive of the compensatory growth during this period due to moderate but not for high SLAA deficiency.…”
Section: Discussionmentioning
confidence: 72%
“…It was observed that for trial 1 (study of Tavernari et al 2012), the estimated SID-ILE requirement for BWG was substantially lower than would be expected from a visual interpretation of the curve. This overestimation of the SID-ILE requirement in trial 1 could be avoided by removing the last observation leaving still some 5 observations on which the curve fitting could be carried out.…”
Section: Resultsmentioning
confidence: 84%